Inventing abstraction 1910-1925 : how a radical idea changed modern art - Dickerman, Leah; Affron, Matthew; Bois, Yve-Alain; Chlenova, Masha; Inventing Abstraction New York. Museum of Modern Art 2012-12, 23 (London : Thames & Hudson, 2012)
This book explores the development of abstraction from the moment of its declaration around 1912 to its establishment as the foundation of avant-garde practice in the mid-1920s. The book brings together many of the most influential works in abstractions early history to draw a cross-media portrait of this watershed moment in which traditional art was reinvented in a wholesale way. Works are presented in groups that serve as case studies, each engaging a key topic in abstractions first years: an artist, a movement, an exhibition or thematic concern. Key focal points include Vasily Kandinskys ambitious Compositions V, VI and VII ; a selection of Piet Mondrians work that offers a distilled narrative of his trajectory to Neo-plasticism ; and all the extant Suprematist pictures that Kazimir Malevich showed in the landmark 0.10 exhibition in 1915.0Exhibition: MoMA, New York, USA (23.12.2012-15.4.2013).
Published in conjunction with the exhibition "Inventing Abstraction", 1910-1925 at the Museum of Modern Art, New York, December 23, 2012 - April 15, 2013
boek
Keywords: Abstracte kunst